Comparison Between the Effect of the Information-Motivation-Behavioral (IMB) Model and Psychoeducational Counseling on Sexual Satisfaction and Contraception Method Used Under the Coercion of the Spouse in Iranian Women: A Randomized, Clinical Trial - Alieh Zarbaf; Atefeh Ahmadi; Elahe Rafati; Faezeh Ghorbani; Masumeh Ghazanfar Pour; Katayoun Alidousti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective Women play an essential role in maintaining the family's health, and family planning is part of women's and families' health. The couple's mutual understanding of family planning methods is essential in selecting contraception. Acceptance of and satisfaction with different contraception methods can impact sexual satisfaction. The present study aimed to compare the effect of the information-motivation-behavioral (IMB) model and psychoeducational counseling on sexual satisfaction and contraception methods of women referring to health centers in Kerman. Methods This trial was conducted on 81 women aged 18 to 45, in Kerman health centers, from 2021 to 2022. Participants were randomly divided into 3 groups of 27 people (control, psychoeducational counseling, and IMB method). Three online counseling sessions were held for the psychoeducational group, and four were held for the IMB group. The control group received routine care. The IBM SPSS Statistics for Windows, version 22 (IBM Corp. Armonk, NY, USA) was used for data analysis using nonparametric Friedman and Kruskal-Wallis tests. Results The mean age of participants was 32.59 ± 7.04, and the majority of them had university degrees and were homemakers. The mean sexual satisfaction score significantly increased immediately after the intervention and 1 month later in the 2 interventional groups (p< 0.0). Changes in contraception methods after intervention were significant in the psychoeducational group (p= 0.0) Conclusion The results indicate the positive impact of psychological counseling on women's sexual satisfaction and contraception method. The IMB method also impacted men's sexual satisfaction but did not lead to any changes in the contraceptive method.